CODEMamb - an observational communication behavior assessment tool for use in ambulatory dementia care - Knebel, Maren; Haberstroh, Julia; Kümmel, Anne; Pantel, Johannes; Schröder, Johannes (Aging & mental health, 2016)
Introduction: Communication improves well-being and quality of life for both people with dementia and their professional and family caregivers. Individualized communication, as required in informed consent procedures and psychosocial interventions, can improve quality of life, especially in ambulatory settings. However, few valid and reliable instruments exist that enable communication to be assessed and communication and behavioral resources to be identified. We, therefore, extended and adapted the newly developed observational instrument CODEM for use in ambulatory settings (CODEMamb).Methods and results: Reliability and validity of the new instrument were studied in a total of 171 patients, whereby principal component analysis revealed three important factors: relationship aspects, verbal communication behavior and nonverbal communication behavior. CODEMambs internal consistency, interrater and retest reliability were satisfactory to excellent. Convergent validity indices, as shown by examining correlations with similar but not identical constructs (CERAD-NP verbal subscales), were medium-high, while the divergent validity index (constructional praxis) was relatively low. The relationship to peer-rating remained nonsignificant. Criterion validity was investigated in groups of patients in accordance with their cognitive status. As expected, verbal communication abilities deteriorate faster than the relationship aspects of communication as the disease progresses.Conclusions: In summary, CODEMamb is a reliable and valid instrument that can be used to collect important information with the ultimate aim of supporting communication with people with dementia.
Published online: 04 Sep 2015
Gesehen am 27.04.2020